Paleoenvironmental Influences Evaluation on Sedimentary Organic Matter of the Kampungbaru Formation, Lower Kutai Basin: Organic and Inorganic Geochemical Approaches - Jamaluddin; Jamaludin, Siti Nur Fathiyah; Massinai, Muhammad Altin; Zhang, Shiqi; Mansor, Hafzan Eva; Oscar, Agus Wiramsya (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
The study of paleoenvironmental influences on sedimentary organic matter has become a critical field of research, particularly in understanding the depositional conditions that control the accumulation and preservation of organic matter. In present study, Upper Miocene-Pliocene Kampungbaru Formation of the Lower Kutai Basin, Indonesia was evaluated by utilizing geochemical proxies to interpret the role of paleoclimate, paleosalinity, and paleoredox conditions on the enrichment of sedimentary organic matter. The rock unit is mostly comprised of shale, coaly shale and coal. The sediments of the Kampungbaru Formation were mostly deposited in a freshwater to brackish depositional environment, likely representing swampy or deltaic settings with transitions between weakly anoxic to oxic environments. A fluctuation between humid and arid climates with higher total organic carbon (TOC) values associated with humid conditions that enhanced  the organic matter preservation. The geochemical results indicate that the analyzed samples have a TOC content between 1.50 wt.% to 43.68 wt.%, indicating a good to excellent organic matter content. Organic matter in the Kampungbaru Formation is composed of type III (gas-prone) and type II-III (mixed oil and gas prone) kerogen, with HI values ranging from 91 to 269 mg HC/g TOC. The pyrolysis Tmax of the Kampungbaru Formation range from 301 to 427 °C which indicate that sediments are thermally immature, bordering on the limit of 435ºC. The closure of the Indonesian Seaway during the Miocene-Pliocene restricted marine water exchange between the Indian and Pacific Oceans. This tectonic event likely reduced marine influence in the Lower Kutai Basin promoting freshwater-dominated depositional settings such as swamps and deltas.